2018
DOI: 10.1177/0363546518763362
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Clinical Outcomes After Hip Arthroscopy: A Prospective Analysis of 1038 Patients With 2-Year Follow-up

Abstract: This study reports favorable clinical outcomes in the largest cohort of hip arthroscopies with a minimum 2-year follow-up in the literature to date. Factors identified as predictive in both bivariate and multivariate analyses included preoperative NAHS, HOS-ADL, and mHHS; age; duration of symptoms; BMI; and revision hip arthroscopy. These predictive factors may be useful to the clinician in determining prognosis and operative indications for hip arthroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
104
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 55 publications
3
104
2
Order By: Relevance
“…Some studies have also identified BMI as a risk factor for poorer patient-reported and clinical outcomes. 12 , 13 , 16 , 27 , 31 Wolfson et al. 12 noted that female sex and BMI >30 were associated with lower rates of achieving a MCID or PASS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also identified BMI as a risk factor for poorer patient-reported and clinical outcomes. 12 , 13 , 16 , 27 , 31 Wolfson et al. 12 noted that female sex and BMI >30 were associated with lower rates of achieving a MCID or PASS.…”
Section: Discussionmentioning
confidence: 99%
“…O ver the past decade, hip arthroscopy has become a routine procedure for the surgical treatment of femoroacetabular impingement syndrome (FAIS), with favorable outcomes and high success rates at short-, mid-, and long-term follow-up. [1][2][3][4][5][6][7][8][9] Yet, as with all orthopaedic procedures, rate of recovery and outcomes are highly influenced by patient-specific factors, including age, sex, body habitus, and arthritic changes. 10,11 Increasing evidence has demonstrated that outcomes of orthopaedic procedures also depend on patient psychological traits, which can affect compliance, rehabilitation effort, and pain perception.…”
mentioning
confidence: 99%
“…Undoubtedly, the benefit of the resolution of the impingement is limited in cases of cartilaginous lesions of sufficient degree to reduce the joint space below 2 mm. This cartilaginous involvement is currently considered the main limitation and one of the major prognostic factors of treatment failure in this type of hips [6].…”
mentioning
confidence: 97%